Importance of the Pre-Requisite Subject - K., Kadirgama; M. M., Noor; M. R. M., Rejab; N. M. Zuki, N. M. (2008)
In this paper, it describes how the pre-requisite subjects influence the student’s performance in Heat transfer subject in University Malaysia Pahang (UMP). The Pre-requisite for Heat transfer in UMP are Thermodynamics I and Thermodynamics II. Randomly 30 mechanical engineering students were picked to analysis their performance from Thermodynamics I to Heat transfer. Regression analysis and Neural Network were used to prove the effect of prerequisite subject toward Heat transfer. The analysis shows that Thermodynamics I highly affect the performance of Heat transfer. The results show that the students who excellent in Thermodynamics I, their performance in Thermodynamics II also the same and goes to Heat transfer. Those students who scored badly in their Thermodynamics I, the results for the Thermodynamics II and Heat transfer are similar to Thermodynamics I. This shows the foundation must be solid, if the students want to do better in Heat transfer.